(untitled) - Okada, Yaichiro (Japan, 1966)
The fishes carried on these illustratons and descriptions are quite typical ones in more tha several hundred, but those we commonly find at fish market and live in the coastal and fresh waters are included, so you many consider them to be only examples of importance in and around Japan.
Keywords: Fishes,Cá; Japan,Nhật Bản